Penggunaan Permainan Puzzle Carakan Dalam Pembelajaran Menulis Aksara Jawa Di Sekolah Dasar - Maryana, Windri; Rahmawati, Laili; Malaya, Krisma Anugra (JURNAL PENDIDIKAN DASAR NUSANTARA, 2021)
Javanese script is one of the subjects that is considered quite difficult for elementary school students. The conventional way of teaching teachers is one of the contributing factors. The use of learning media using educational games is one solution for teachers in teaching. Puzzles are a form of innovation that can be used to stimulate children's brains. Playing while learning will make children more interested so that children will not feel bored quickly. The aims of this study are: (a) To find out the mechanism of using Puzzle Carakan media in learning to write Javanese script. (b) To find out how the effect of using Puzzle Carakan media in learning write Javanese characters. This type of research uses a qualitative descriptive approach. The data analysis technique used is by analyzing student answers, as well as comparing student learning outcomes before learning to use Puzzle Carakan and after using Puzzle Carakan.